Kingella kingae infections in paediatric patients: 5 cases of septic arthritis, osteomyelitis and bacteraemia - Birgisson, H; Steingrimsson, O; Gudnason, T (Scandinavian Journal of Infectious Diseases, 2010)
To access publisher full text version of this article. Please click on the hyperlink in Additional Links field Kingella kingae is a Gram-negative rod most often recognized as 1 of the organisms causing septic arthritis and osteomyelitis in children. Infection caused by K. kingae had not been diagnosed in Iceland until 5 cases were diagnosed at the Paediatric Department at the University Hospital of Iceland over a 1 year period. In this report we describe these 5 children with invasive infection caused by K. kingae (2 with septic arthritis, 1 with osteomyelitis, 1 with septic arthritis and osteomyelitis, and 1 with bacteraemia) and review the literature. All bacterial isolates were identified by the Bactec culture system.